High Coral Recruitment Despite Coralline Algal Loss Under Extreme Environmental Conditions - Tanvet, Clément; Benzoni, Francesca; Peignon, Christophe; Thouzeau, Gérard; Rodolfo-Metalpa, Riccardo (Frontiers in Marine Science, 2022)
The crucial role of crustose coralline algae (CCA) in inducing hard coral larval settlement and ensuring the replenishment of coral reefs is widely accepted, and so are the negative effects of anthropogenic CO2 emissions on both CCA abundance and coral development. However, diversified and well-developed coral reef communities have been recently discovered in natural conditions where CCA and corals would not be expected to thrive. Back-reef pools, volcanic CO2 vents, mangrove estuaries, and semi-enclosed lagoons systems can present seawater pH, temperature, and dissolved oxygen values reaching or even exceeding the conditions currently predicted by the IPCC for 2100. In the semi-enclosed lagoon of Bouraké (New Caledonia, southwest Pacific Ocean), seawater pHT, dissolved oxygen, and temperatures regularly fluctuate with the tide reaching respectively minimum values of 7.23 pHT units, 2.28 mg O2 L-1, and maximum of 33.85°C. This study reports the effect of such extreme environmental conditions on hard coral recruitment and CCA originally settled at a forereef on artificial substrates that were transplanted over two years in at two fringing reefs and a the Bouraké lagoon. Our data emphasize the negative effects of the extreme conditions in our study sites on the CCA, which decreased in cover by ca. 80% and lost in the competition with turf algae, which, in turn, increased up to 162% at the end of the two years. Conversely, hard coral recruitment remained high at Bouraké throughout the study, three-fold higher than at two sites located outside Bouraké where environmental conditions were typical for coastal fringing reefs. Our findings show that while such extreme, climate change like-conditions have a direct and adverse effect on CCA abundance, and despite a certain persistence, coral larvae settlement was not affected. Based on previous findings from Bouraké, and the present observations, both coral recruits and adults seem to be unaffected despite the extreme environmental conditions. This study supports previous research illustrating how extreme natural and variable environments may reveal unexpected and positive insights on the processes underlying coral acclimatization and adaptation to global change.